Equilibrium, Kinetic and Thermodynamic Investigation of Adsorption of Hexavalent Chromium by Activated Carbon Derived from Leucaena leucocephala Seed Pod - Yusuff, Adeyinka Sikiru; Nwosu, Chisom Joy (Universitas Gadjah Mada)
In the present study, Leucaena leucocephala seed pod, a non-edible plant waste, was utilized to prepare low-cost activated carbon to remove hexavalent chromium [Cr(VI)] from aqueous solution via batch mode adsorption. The activated carbon was prepared by chemical activation with NaOH and characterized by Brunauer-Emmett-Teller (BET) surface area measurement, Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) spectroscopy. The effects of various variables, such as initial Cr(VI) concentration, contact time, adsorbent dosage, temperature, and pH, which influence the adsorption processes, were investigated. Equilibrium adsorption isotherms, the kinetic and thermodynamic behavior of the process were investigated. The obtained results showed that 100 min contact time, 1.0 g adsorbent dose, 45 °C temperature and solution pH of 6.0 resulted in maximum Cr(VI) uptake. The experimental data well fitted to the Langmuir isotherm with monolayer adsorption capacity of 26.94 mg/g. The kinetic analysis showed that the pseudo-second-order model well fitted to the acquired experimental data. The thermodynamic behavior of Cr(VI) adsorption onto activated carbon was found to be spontaneous and endothermic. The L. leucocephala seed pod based activated carbon was found to be efficient for Cr(VI) adsorption.